Orientational self-sorting in cuboctahedral Pd cages. Issue 40 (6th October 2022) - Li, Ru-Jin; Tarzia, Andrew; Posligua, Victor; Jelfs, Kim E.; Sanchez, Nicolas; Marcus, Adam; Baksi, Ananya; Clever, Guido H.; Fadaei-Tirani, Farzaneh; Severin, Kay
Abstract : Cuboctahedral [Pd12 L24 ] 24+ cages based on low-symmetry ligands can potentially form a vast number of isomers, but the self-assembly process was found to be highly selective. Abstract : Cuboctahedral coordination cages of the general formula [Pd12 L24 ] 24+ (L = low-symmetry ligand) were analyzed theoretically and experimentally. With 350 696 potential isomers, the structural space of these assemblies is vast. Orientational self-sorting refers to the preferential formation of particular isomers within the pool of potential structures. Geometric and computational analyses predict the preferred formation of cages with a cis arrangement at the metal centers. This prediction was corroborated experimentally by synthesizing a [Pd12 L24 ] 24+ cage with a bridging 3-(4-(pyridin-4-yl)phenyl)pyridine ligand. A crystallographic analysis of this assembly showed exclusive cis coordination of the 3- and the 4-pyridyl donor groups at the Pd 2+ ions.